Procladius travassosi (Oliveira, Messias & Silva-Vasconcelos, 1992) regarded as a new junior synonym of Procladius stroudi Roback 1982 (Diptera: Chironomidae: Tanypodinae) - Da Silva, Fabio Laurindo (Zootaxa, 2019)
Although recent years have seen increased activity regarding chironomid systematics in the Neotropical region (e.g. Oliveira et al. 2011, 2013, Trivinho-Strixino et al. 2013, 2015, Amora et al. 2015, Parise & Pinho 2016, Andersen et al. 2017, Silva & Song 2018, Trivinho-Strixino & Silva 2018), particularly concerning the subfamily Tanypodinae (e.g. Oliveira & Silva 2011, Silva & Wiedenbrug 2015, Silva et al. 2014a,b; Siri et al. 2015, Silva & Oliveira 2016, Silva & Ferrington 2018), when it comes to some species-rich groups, such as Djalmabatista Fittkau, Larsia Fittkau and Procladius Skuse, the taxonomic knowledge remains fragmentary, with only a few species recorded to the Neotropics.